Application of Silver Conducting Glasses to Solid State Batteries and Sensors. (1990) - Jun, Liu; Portier, J.; Tanguy, B.; Videau, J. J.; Ait Allal, M.; Morcos, J.; Salardenne, J.
Abstract : Fast silver ion conducting glasses as electrochemical devices have been tested. A silver iodine battery using a silver ionic conducting glass (AgPO3 -Ag2 S-AgI) has been studied. The interaction of some gases (O2 CI2, H2 S) with the electrochemical chains: Pt/Sb2 S3 -AgI (glass)/Ag and Pt/AgCl (thin film)/Sb2 S3 - AgI (glass)/Ag has been investigated. Finally, the behavior of thin films of Ag2 S3 -Ag2 S-CdS glasses as sensitive membranes for Cd detection in solution has been tested on MIS structures Au/Si/SiO2 / Membrane/Cd in solution/Reference electrode.